2020
DOI: 10.2147/idr.s264805
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Sub-Minimum Inhibitory Concentrations of Tyrosol and EDTA on Quorum Sensing and Virulence of <em>Pseudomonas aeruginosa</em></p>

Abstract: Introduction: Pseudomonas aeruginosa is considered a dangerous pathogen, as it causes many human diseases, besides that it is resistant to almost all types of antibacterial agents. So, new strategies to overcome P. aeruginosa infection have evolved to attenuate its virulence factors and inhibit its quorum-sensing (QS) activity. Purpose: This study investigated the effect of tyrosol and EDTA as anti-quorum-sensing and antivirulence agents against P. aeruginosa PAO1. Methods: Anti-quorum activity of sub-minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For example, cinnamic acid is induced by beneficial Rhizobia bacteria in rice and is implicated in resistance to Rhizoctonia (Mishra et al, 2006). Another polyphenol called tyrosyl was shown to have very potent antifungal activity not only in plant diseases but also in human infections (Abdel-Rhman et al, 2020;Berne et al, 2020). Sinapinaldehyde or Sinapyl aldehyde is another class of antifungal compound produced naturally in plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cinnamic acid is induced by beneficial Rhizobia bacteria in rice and is implicated in resistance to Rhizoctonia (Mishra et al, 2006). Another polyphenol called tyrosyl was shown to have very potent antifungal activity not only in plant diseases but also in human infections (Abdel-Rhman et al, 2020;Berne et al, 2020). Sinapinaldehyde or Sinapyl aldehyde is another class of antifungal compound produced naturally in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of AA on the expression levels of P. aeruginosa QS circuit genes (i.e., lasR, rhlR, rhlI, rhlA, and pqsA) and T3SS circuit genes (i.e., exoT, exoS, exsA, and exoY) and the flagellin gene (fliC) were evaluated by qRT-PCR, as described previously [35][36][37][38]. P. aeruginosa TL1671 and TL2314 was incubated in fresh LB broth at 37℃ under 180 rpm until reaching the logarithmic growth phase (OD 600 0.5-0.6).…”
Section: Quantitative Reverse Transcription Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Swimming, swarming and twitching are three forms of motility in P. aeruginosa that are positively controlled by the LasIR and RhIR QS systems; las regulating swimming, swarming and twitching; and rhI controlling swarming and twitching (Yeung et al, 2009 ). Abdel-Rhman et al, ( 2020 ) found that tyrosol (1/4 ×—1/16 × MIC) significantly decreased both swimming and swarming motility, but had no effect on twitching motility. Our study shows that regulation of gene expression differs significantly between strains and in the presence of similar treatments (QQ) (Figs.…”
Section: Discussionmentioning
confidence: 99%